A hydrogel stamper with expandable height and built-in reservoirs for patterning biomolecules on 3D topologies - Wan Salim, Wan Wardatul Amani; Ding, Zhenweng; Ziaie, Babak (IEEE, 2008)
In this paper, we report on an expandable height hydrogel stamper with built-in reservoir that can be used to repeatedly (without frequent re-inking) stamp functional biomolecules on planar and non-planar surfaces. We have successfully patterned fluorescein isothiocyante (FITC) labeled antibodies (antibodies for O-antigens of Bradyrhizobium japonicum made in rabbits) on planar (silicon) and nonplanar (SU8 on silicon with a height of ~ 70µm) topologies. The printed antibodies show the effectiveness of hydrogel stampers in delivering biomolecules on 3D topologies where the hydrogel could be adjusted to stamp on the sidewalls and bottom of deep trenches.